GERAKAN DAKWAH PADA ORGANISASI NAHDLATUL WATHAN - Hafizul Arifin, Muhammad (Qaulan Baligha: Jurnal Ilmu Manajemen Dakwah, 2025)
Nahdlatul Wathan is the largest organization in NTB. This organization was born in Pancor, East Lombok in 1953 AD. His stance was motivated by the rapid development of madrasah branches NWDI (Nahdlatul Wathan Diniyah Islamiyah) and NBDI (Nahdlatul Banat Diniyah Islamiyah). So that an organizational body is needed that oversees the large number of madrasas. This organizational movement moves in three main focuses, namely social, da'wah and education. This research uses a descriptive qualitative method sourced from books related to the organization of Nahdlatul Wathan. The findings in this study are that the success of the da'wah movement is greatly influenced by the methods used and the appropriate response to the local social environment. There are at least four consciousness as a social response that can be seen in the Nahdlatul Wathan organization's da'wah movement: 1). Religious awareness, 2). Awareness of the importance of science, 3). Awareness of organization and society, 4). Awareness as a nation.